2003
DOI: 10.1042/bst0311433
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of in vivo 3-deoxyglucosone levels

Abstract: Fructoselysine 3-phosphate is synthesized in vivo by the recently discovered fructoseamine-3-kinase (F3K) from fructoselysine and ATP and decomposes to lysine, P(i) and 3-deoxyglucosone (3DG). This pathway appears to dominate 3DG production in vivo, making it possible to modulate 3DG levels by stimulating or inhibiting the reaction. Present inhibitors are non-reacting substrate analogues with relatively high K (i) values and can inhibit F3K sufficiently in vivo to reduce 3DG in diabetic rat plasma by approx. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Increased 3-DG has been shown to lead to a threefold increase in kidney lesions after 3 days in a rat model [32]. Among the patients in our study, we observed an eightfold increase in serum 3-DG after receiving 1.7 l of GDP-containing infusion fluid.…”
Section: Discussionsupporting
confidence: 54%
“…Increased 3-DG has been shown to lead to a threefold increase in kidney lesions after 3 days in a rat model [32]. Among the patients in our study, we observed an eightfold increase in serum 3-DG after receiving 1.7 l of GDP-containing infusion fluid.…”
Section: Discussionsupporting
confidence: 54%
“…Although the functions of FN3K homologs in lower eukaryotes and bacteria are yet to be equivocally established, it is proposed that they repair proteins modified by ribose-5-phosphate, a potent glycating agent generated by the metabolic pentose phosphate pathway (6,12,14,15). FN3K activity is essential for normal cellular functions, and uncontrolled activity can result in altered cellular homeostasis and disease (16,17). For example, accumulation of 3-deoxyglucosone, a by-product of human FN3K (HsFN3K) activity, is causatively associated with diabetic complications, such as retinopathy and neuropathy (18,19), and the development of hepatocellular carcinoma is dependent on the deglycation of nuclear transcription factor NRF2 (encoded by nuclear factor erythroid-derived 2-like 2 gene; NFE2L2) by HsFN3K (20).…”
Section: Introductionmentioning
confidence: 99%
“…Since the protein deglycation pathway is predominated by FN3K, it has been suggested by Brown et al [2003] that it may be possible, using FN3K specific inhibitors, to reduce the formation of 3-DG. 1-Deoxy-1-morpholinofructose (DMF) was originally employed as an FN3K inhibitor (K i 5 100 mM) for demonstrating the enzymatic process of hemoglobin deglycation, but DMF is, in fact, a substrate (K m 5 100 mM) for FN3K [Delpierre et al, 2000b[Delpierre et al, , 2002Delpierre and Van Schaftingen, 2003].…”
Section: Introductionmentioning
confidence: 99%